The Mediating Role of Customer Satisfaction in the Influence of Product Quality and Service Quality on Customer Loyalty at Saos Ratih MSME in Bekasi: - I Made Wahyu Surya Pranata; I Wayan Adi Wikantara (Universitas Dehasen Bengkulu, 2026)
The purpose of this study is to examine how customer satisfaction influences the effect of product quality and service quality on customer loyalty at the Saos Ratih MSME in Bekasi. The research was conducted using a quantitative approach with 64 respondents and analyzed using SmartPLS. The findings indicate that product quality has a positive effect on both customer satisfaction and customer loyalty, while service quality only affects customer satisfaction but does not influence loyalty. Customer satisfaction positively affects loyalty; however, it does not effectively mediate the relationship between product quality, service quality, and customer loyalty. Overall, product quality plays a more decisive role in shaping customer loyalty, whereas service quality contributes more to enhancing customer satisfaction.